2004
DOI: 10.1038/sj.bjp.0705889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabinoid receptor‐2 activation on accelerated gastrointestinal transit in lipopolysaccharide‐treated rats

Abstract: 1 The biological effects of cannabinoids (CB) are mediated by CB 1 and CB 2 receptors. The role of CB 2 receptors in the gastrointestinal tract is uncertain. In this study, we examined whether CB 2 receptor activation is involved in the regulation of gastrointestinal transit in rats. 2 Basal and lipopolysaccharide (LPS)-stimulated gastrointestinal transit was measured after instillation of an Evans blue-gum Arabic suspension into the stomach, in the presence of specific CB 1 and CB 2 agonists and antagonists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
138
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 52 publications
17
138
3
1
Order By: Relevance
“…In this issue of the British Journal of Pharmacology, Mathison et al (2004) provide pharmacological evidence that the CB 1 -mediated reduction of gastrointestinal transit was absent in rats treated with an endotoxic inflammatory agent, being replaced by a CB 2 -mediated inhibition of stimulated transit. It is reported that the selective CB 2 receptor agonist JWH-133 was without effect in control animals, but it reduced the increase in gastrointestinal transit induced by intraperitoneal administration of lipopolysaccharide (LPS).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In this issue of the British Journal of Pharmacology, Mathison et al (2004) provide pharmacological evidence that the CB 1 -mediated reduction of gastrointestinal transit was absent in rats treated with an endotoxic inflammatory agent, being replaced by a CB 2 -mediated inhibition of stimulated transit. It is reported that the selective CB 2 receptor agonist JWH-133 was without effect in control animals, but it reduced the increase in gastrointestinal transit induced by intraperitoneal administration of lipopolysaccharide (LPS).…”
mentioning
confidence: 98%
“…Consistent with these in vitro studies, cannabinoid receptor agonists reduce gastric, small intestinal and colonic motility in rodents in vivo, an effect counteracted by the selective CB 1 receptor antagonist SR141716A, but not by the selective CB 2 receptor antagonist SR144528. Interestingly, a CB 1 -mediated reduction of intestinal motility has been observed also in some pathophysiological states in mice, including the experimental ileus induced by intraperitoneal administration of acetic acid and the model of intestinal inflammation induced by oral croton oil (for a review, see Di Carlo & Izzo, 2003).In this issue of the British Journal of Pharmacology, Mathison et al (2004) provide pharmacological evidence that the CB 1 -mediated reduction of gastrointestinal transit was absent in rats treated with an endotoxic inflammatory agent, being replaced by a CB 2 -mediated inhibition of stimulated transit. It is reported that the selective CB 2 receptor agonist JWH-133 was without effect in control animals, but it reduced the increase in gastrointestinal transit induced by intraperitoneal administration of lipopolysaccharide (LPS).…”
mentioning
confidence: 99%
“…A large body of evidence has emerged over the last two decades from a plethora of in vivo studies, which have been performed almost exclusively on the mouse and rat (Pertwee, 2001), that the predominant action of psychotropic cannabinoids on the intestinal tract is a reduction in the propulsive (Colombo et al, 1998;Izzo et al, 1999;2001;Landi et al, 2002;Mathison et al, 2004;Carai et al, 2006) and secretory (Shook and Burks, 1989;Izzo et al, 1999; function of the small intestine. The former action has been invariably studied by evaluating either the distance travelled or the delay in the time taken for the transit of an orally or intra-duodenally administered non-absorbable marker from the pylorus to the caecum of the animal.…”
Section: Introductionmentioning
confidence: 99%
“…Although the guinea pig ileum has long served as a useful bioassay for describing the inhibitory action of cannabinoids on intestinal transit observed in the mouse or rat in vivo, it is important that isolated ileal tissues from the latter species are used for studying cannabinoid effects. First, because a large number of models of disturbed intestinal motility of man have been created using the rat and mouse (Izzo et al, 1999;2001;Mascolo et al, 2002;Mathison et al, 2004), and second, to date, the guinea pig has not been employed for investigating cannabinoid effects on ileal transit in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent report showed that experimental colitis is more severe in CB1-deficient mice than in wild-type littermates, and furthermore, that pre-treatment with a CB1 antagonist in wild-type mice elicits a similar potentiated susceptibility to this experimental colitis model [97]. Further recent evidence suggests the possibility that CB2 receptors in the rat intestine can help reduce the increase of intestinal motility induced by endotoxic inflammation [99]. By minimizing the adverse psychotropic effects associated with brain cannabinoid receptors, the CB2 receptor represents a promising molecular target for the treatment of motility disorders from the perspective of reduced side effects.…”
Section: Gastrointestinalmentioning
confidence: 99%